Homologous or heterogenous vaccination boosters enhance neutralizing activities against SARS‐CoV‐2 Omicron BA.1 variant. Issue 2 (11th May 2022) - Zhou, Zhongcheng; Du, Peng; Li, Ning; Xiong, Xinxin; Tang, Shengjun; Dai, Qinjin; Wang, Taorui; Yu, Meixing; Man, Miao; Lam, Kelvin; Baptista‐Hon, Daniel T.; Tai, Wa Hou; et al.
Abstract: The SARS‐CoV‐2 Omicron BA.1 variant of concern contains more than 30 mutations in the spike protein, with half of these mutations localized in the receptor‐binding domain (RBD). Emerging evidence suggests that these large number of mutations impact the neutralizing efficacy of vaccines and monoclonal antibodies. We investigated the relative contributions of spike protein and RBD mutations in Omicron BA.1 variants on infectivity, cell–cell fusion, and their sensitivity to neutralization by monoclonal antibodies or vaccinated sera from individuals who received homologous (CoronaVac, SinoPharm) or heterologous (CoronaVac—BNT162b2, BioNTech) and nonhuman primates that received a recombinant RBD protein vaccine. Our data overall reveal that the mutations in the spike protein reduced infectivity and cell–cell fusion compared to the D614G variant. The impaired infectivity and cell–cell fusion were dependent on non‐RBD mutations. We also find reduced sensitivity to neutralization by monoclonal antibodies and vaccinated sera. However, our results also show that nonhuman primates receiving a recombinant RBD protein vaccine show substantial neutralization activity. Our study sheds light on the molecular differences in neutralizing antibody escape by the Omicron BA.1 variant, and highlights the promise of recombinant RBD vaccines in neutralizing the threat posed by the Omicron BA.1 variant. Abstract : Sera from vaccine recipients of the regimen shown was evaluated for neutralizing activity against Omicron BA.1. All sera showed impaired neutralizing activity against the Omicron BA.1. However, our results show that the efficacy of a heterologous booster regimen (two doses of CoronaVac followed by the BNT162b2 vaccine) elicited stronger neutralizing activity than a homologous booster regimen (three doses of the CoronaVac vaccine) against both D614G and Omicron BA.1 pseudoviruses.